Effective Military-Patriotic Education of Servicemen of Armed Forces of Ukraine - Stadnik, Vadym (Pedagogical Discourse, 2011)
In the article the necessity of a technology of military-patriotic education of the Armed Forces of Ukraine at the level of simulation content, forms and methods for the purpose of education. The author of the basic components of the technologies of military-patriotic education, which in their complex use can increase the efficiency of patriotic outlook personality.